Needle tract seeding in renal tumor biopsies: experience from a single institution - Yan Zhou; Paari Murugan; Faqian Li; Lihong Bu (BMC, 2021)
Abstract Background Percutaneous needle biopsy of renal masses has been increasingly utilized to aid the diagnosis and guide management. It is generally considered as a safe procedure. However, tumor seeding along the needle tract, one of the complications, theoretically poses potential risk of tumor spread by seeded malignant cells. Prior studies on the frequency of needle tract seeding in renal tumor biopsies are limited and clinical significance of biopsy-associated tumor seeding remains largely controversial. Methods Here we investigated the frequencies of biopsy needle tract tumor seeding at our institution by reviewing the histology of renal cell carcinoma nephrectomy specimens with a prior biopsy within the last seventeen years. Biopsy site changes were recognized as a combination of foreign body reaction, hemosiderin deposition, fibrosis and fat necrosis. The histologic evidence of needle tract tumor seeding was identified as clusters of tumor cells embedded in perinephric tissue spatially associated with the biopsy site. In addition, association between parameters of biopsy techniques and tumor seeding were investigated. Results We observed needle tract tumor seeding to perinephric tissue in six out of ninety-eight (6 %) renal cell carcinoma cases including clear cell renal cell carcinoma, papillary renal cell carcinoma, chromophobe, and clear cell papillary renal cell carcinoma. The needle tract tumor seeding was exclusively observed in papillary renal cell carcinomas (6/28, 21 %) that were unifocal, small-sized (≤ 4 cm), confined to the kidney and had type 1 features. No recurrence or metastasis was observed in the papillary renal cell carcinoma cases with tumor seeding or the stage-matched cases without tumor seeding. Conclusions Our study demonstrated a higher than reported frequency of needle tract tumor seeding. Effective communication between pathologists and clinicians as well as documentation of tumor seeding is recommended. Further studies with a larger patient cohort and longer follow up to evaluate the impact of needle tract tumor seeding on long term prognosis are needed. This may also help reach a consensus on appropriate pathologic staging of renal cell carcinoma when the only site of perinephric fat invasion is within a biopsy needle tract.